IMPACT OF THE LEGAL DEFAULT ON MICRO BUSINESS LOAN RECIPIENTS - Henry Kristian Siburian (SEAN Institute, 2022)
. Micro Business Credit (KUM) is a type of soft loan which: is intended for Micro, Small and Medium Enterprises (MSMEs) with business feasibility but limited capital. It can be seen that if the credit recipient or debtor defaults into the main problem in the Micro Business Loan Agreement. Thus, the banking institution as the party providing the credit will cause an indication of default by the debtor which results in losses for the bank providing the credit. The type of research used in this study from the point of view of its nature is normative research (juridical normative) legal research conducted by examining library materials. Based on research resultsThe provision of Micro, Small and Medium Business Credit cannot be separated from the legal aspect of the assignment/agreement, namely the existence of two parties that bind themselves, namely the bank as the borrower.The rights and obligations of micro business credit recipients, namely micro business credit customers have the right to know the products offered. The debtor's default includes debtors who have wrong achievements, debtors who are slow in the process of completing presentations.